MANAGEMENT AUDIT IN SUPPORTING ECONOMIZATION, EFFICIENCY, AND EFFECTIVENESS AT PT. BPR RAMBI ARTHA PUTRA - Anindita, Dayinta; Rachmawati, Lia; Kartika Sari, Nurshadrina (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2022)
This research was conducted aimed at assessing or evaluating managemen performance from the Management Audit aspect in supporting the economization of efficiency, and effectiveness at PT. BPR Rambi Artha Putra. The research method used in this study is q qualitative research method with a case study approach. The results of this study indicate that examining the company’s operational activities using managemen audits, human resource management audits and marketing management audits has supported the company’s effectiveness and efficiency but has not supported the company’s economics, and financial management audits have supported the company’s economy efficiency and effectiveness.